How will the financial crisis affect health?. (1st April 2009) - Marmot, M G; Bell, Ruth
Abstract : Global recession is likely to damage our health as well as our wealth, but it also offers an opportunity to build a more equitable economic model as Michael Marmot and Ruth Bell explain in light of the G20 summit